The Neurogenetics of Racial Injustice: Oxytocin Receptor (OXTR) Gene rs53576 is ASSOCIATED with Perceived Discrimination and Other-Oriented Justice Beliefs in African Americans - Drolet, Caroline E. (Race and social problems, 2021)
According to the social salience hypothesis, the neuropeptide oxytocin boosts attunement to both positive and negative social cues, such that the effects of oxytocin on social beliefs and behavior are highly dependent on context. Among underserved racial minorities, oxytocin might enhance sensitivity to racial injustice. To test this hypothesis, we examined whether the oxytocin receptor gene (OXTR) rs53576 polymorphism affects individual differences in both perceived racial discrimination and beliefs about justice in an underserved racial minority. Healthy African Americans (n = 118) provided bloodspot samples that were assayed for the single nucleotide polymorphism (SNP) rs53576. Participants also completed individual differences measures of perceived racial discrimination and beliefs about justice for self and others. Consistent with the social salience hypothesis, individuals with greater potential oxytocin receptivity (G/G genotype) reported greater perceived discrimination than individuals with lower potential oxytocin receptivity (non-G/G genotype; p = .009). Also consistent, G/G individuals had stronger other-oriented beliefs about justice than non-GG individuals (p = .085). Path analysis supported that perceived discrimination mediated the connection from the G/G genotype to stronger other-oriented procedural justice beliefs, suggesting that justice beliefs among African Americans might partly reflect evaluations of discriminatory experiences that stem from oxytocin receptivity.